Efficacy and safety of modified-release prednisone in patients with rheumatoid arthritis - Krasselt M; Baerwald C (Dove Medical Press, 2016)
Marco Krasselt, Christoph Baerwald Rheumatology Unit, Clinic for Gastroenterology and Rheumatology, Department of Internal Medicine, Neurology and Dermatology, University of Leipzig, Leipzig, Germany Abstract: The introduction of modified-release (MR) prednisone adds a drug with encouraging potential to the armamentarium of the rheumatologist. In particular, for patients experiencing a reduced quality of life due to prolonged morning stiffness, it is a promising therapeutic approach. Two clinical trials and one open-label observational study investigated the effectiveness of MR prednisone in reducing rheumatoid arthritis-related morning stiffness for both new and current users of corticosteroids. The efficacy and safety of MR prednisone use in rheumatoid arthritis patients are reviewed in this article. This includes pivotal trials as well as pathophysiological considerations and clinical implications. Keywords: modified-release prednisone, rheumatoid arthritis, efficacy, chronotherapy, HPA axis, side effects, low-dose prednisone